AI-Enabled Job Characteristics, Digital Self-Efficacy, and Innovative Work Behavior: The Mediating Role of Work Engagement - Wachyu Hari Haji (Lembaga Riset Ilmiah, 2024)
This study investigates how AI-enabled job characteristics and digital self-efficacy influence innovative work behavior through work engagement. This study responds to the growing use of artificial intelligence in employee work processes, where AI shapes information access, task completion, decision-making, and idea development.. The originality of this study lies in positioning AI-enabled job characteristics as a technology-based job resource and digital self-efficacy as a personal digital resource that may encourage innovation through employee engagement. A quantitative approach with an explanatory research design was applied. Data were collected using questionnaires from 246 employees who use AI in their daily work, including employees in technology companies, digital banks, financial services, and app-based administrative roles. The data were analyzed using Partial Least Squares Structural Equation Modeling. The findings show that AI-enabled job characteristics and digital self-efficacy have positive and significant effects on work engagement. Work engagement also has a positive and significant effect on innovative work behavior. However, AI-enabled job characteristics and digital self-efficacy do not have significant direct effects on innovative work behavior. The indirect effect results confirm that work engagement fully mediates the relationship between AI-enabled job characteristics and innovative work behavior, as well as the relationship between digital self-efficacy and innovative work behavior. These findings suggest that AI-supported work and digital confidence do not automatically lead to employee innovation unless they first strengthen employee engagement. This study contributes to digital human resource management literature and offers practical insight for organizations seeking to promote innovation through AI-based work design, digital capability development, and stronger work engagement.